The Comparison Between Online and Offline Learning Modes in English Speaking at SMP Negeri 6 Kabupaten Sorong - Rein Lobat; Agus Setiawan (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This study aimed to compare students’ speaking performance and engagement between online and offline classes in English learning at the seventh grade of SMP Negeri 6 Kabupaten Sorong. The research was motivated by the shift in learning modes following the pandemic, which created differences in how students practiced and developed speaking skills. While online learning provided flexibility and digital exposure, offline classes allowed more direct interaction and immediate feedback from teachers. This research used a comparative quantitative design. The population consisted of all seventh-grade students, with two classes selected through purposive sampling: one representing online learning and the other offline instruction. Data were collected using a speaking performance test and a student questionnaire. The test assessed pronunciation, fluency, vocabulary, grammar, and confidence, while the questionnaire measured motivation and learning preferences. The results were analyzed using descriptive statistics and an independent sample t-test to determine whether there was a significant difference between the two groups. The findings showed that students in offline classes achieved higher speaking scores than those in online classes. The mean score of the offline group was 77.25, while the online group’s mean score was 70.80, with a p-value of 0.002 (< 0.05), indicating a significant difference. However, the questionnaire results revealed that students in both modes valued speaking practice, though offline learners benefited more from face-to-face interaction and corrective feedback. It can be concluded that offline learning remains more effective for improving speaking achievement among junior high school students, though online learning still provides meaningful exposure and flexibility when properly guided.